Invoicing Currency and Symmetric Pass-Through of Exchange Rates and Tariffs : Evidence from Malawian Imports from the EU - Montfaucon, Angella Faith (World Bank, Washington, DC, 2021)
The response of import prices to exchange rates can be used to predict the effect of changes in trade policy. The hypothesis of symmetric pass-through of tariffs and exchange rates asserts that the effect of tariffs and exchange rates on prices are identical. This paper examines whether the symmetry hypothesis holds in the context of invoicing currency, by investigating the role of the euro and the U.S dollar currencies. The paper uses transaction-level data of Malawian imports from the European Union (EU) over a 12-year period, separating imports from the Economic and Monetary Union (EMU) members and non-members and across sectors. The findings show that the dollar has the highest invoicing share, and the pass-through rate of exchange rate and tariff shocks on to Malawian consumers is high. Symmetry holds when bilateral exchange rates are used, but when the invoicing currency is considered there are deviations from symmetry. This result implies that to predict the effects of trade policy based on import prices' responses to the exchange rate, bilateral exchange rates are not suitable for capturing exchange rate and tariff pass-through. The variations in the results across EMU and non-EMU, currencies, and industries demonstrates that that empirical evidence is needed in each case to understand the extent of pass-through, which is crucial for import-dependent developing countries such as Malawi.